COSTS OF TRAINING NURSES IN THE INSERTION, REVISION, AND REMOVAL OF INTRAUTERINE DEVICES - Nogueira, Juliana da Silva; Souza, Karla Romana Ferreira de; Lins, Evelyn da Silva Ferreira; Oliveira, Elizandra Cassia da Silva; Lima, Edgard Leonardo Nery Meira; Bezerra, Adriana Falangola Benjamin (Cogitare Enfermagem, 2024)
Objective: To analyze the costs of training in reproductive planning, with nurses’ insertion, revision, and removal of intrauterine devices. Method: Case study, with data collected between May and December 2022, in Recife, Pernambuco, Brazil. The micro-costing evaluation was carried out using absorption costing. Results: Data from five classes in 2022 were analyzed, totaling 70 nurses, and the expenses and direct and indirect costs of offering the course were identified. The cost per class was R17,846.89/U3,307.79), with an average of R1,820.38 or U337.39/student/edition. Compared to other similar courses, it is considered a low-cost course with promising results for the quality of sexual and reproductive health care. Conclusion: Investing in training nurses in reproductive planning helps to reduce the indicators of maternal and child morbidity and mortality associated with unplanned pregnancies.